Irrigation and rain-fed crop production system in Ethiopia - Hordofa, T.; Menkir, Michael; Awulachew, Seleshi Bekele; Erkossa, Teklu (2008)
Crop production is a function of water, nutrient, climate and soil environment. Provided that all other requirement are satisfactorily for proper growth and production, rainfall rarely meets the time with required amount of water application for plant growth. As a result average yield of agricultural crops under rain-fed agriculture is low compared to irrigated agriculture. This study assesses irrigation and rain-fed agriculture system in connection to its potential productivity under existing practice. While the rain-fed areas considered in this study are the aggregate at the national level, five systematically selected Medium and large scale irrigation schemes were selected based on cropping patter, geographic and agro ecological representation These are Fincha?a, MAAE, Metehara, Sille, and UAAIE which are located at three river basins, viz, Nile (Abbay), Awash and the Rift valley basins. Data were collected using pre-formulated checklists, through series of interviews and discussions; and from published and unpublished documents. The result indicated that crop production was undulating under rain-fed agriculture and as a result the performance of rain-fed productivity remained low and stable for most crops. Although crops grown by smallholder private farmers are different, cereals occupy about 74 per cent followed by pulses and oil seeds with small proportion. During the last one decade, the maximum and minimum cultivated land by small-holder peasant farmers at the national level was 10.7 and 6.6 M ha, respectively. Increased cultivable area by private small-holder farmers could not seem to contribute to the increased production. Total irrigated land by private peasant farmers ranged between 66 and 147 thousand hectares for the last one decade. During the last decade the area under irrigation was steadily increasing for most of the large scale schemes. Particularly Fincha?a and Metehara farms are significantly increasing while MAAE farm has shown only a slight increase. At UAAIE farm, crop production shows a decreasing trend. Productivity of banana at Sille farm was decreasing despite its increasing in land area.